2016
DOI: 10.1111/anec.12402
|View full text |Cite
|
Sign up to set email alerts
|

Interventricular conduction disorders after orthotopic heart transplantation: risk factors and clinical relevance

Abstract: RBBB is the most common IVCD. Its presence can be explained by a susceptibility of the right branch to heart positioning, pressure overload, and acute rejection. IVCDs do not affect prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 14 publications
0
27
2
Order By: Relevance
“…11 RBBB is a frequently reported abnormality after orthotopic heart transplant, with reported incidence from 14% to 69%. [12][13][14] In our study, 52% of patients had RBBB. However, the clinical significance is controversial.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…11 RBBB is a frequently reported abnormality after orthotopic heart transplant, with reported incidence from 14% to 69%. [12][13][14] In our study, 52% of patients had RBBB. However, the clinical significance is controversial.…”
Section: Discussionmentioning
confidence: 44%
“…In most studies, researchers found no association between RBBB and adverse outcomes. [12][13][14][15] To our knowledge, a relationship between RBBB and rejection has been reported in only 3 studies, 13,16,17…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since the right bundle branch has a unique anatomical structure, it might be susceptible to damage during HT: much of its septal course is near the endocardium and consists of narrow cylindrical tubes 17. Also, biatrial anastomosis and clockwise rotation of a transplanted heart, as a result of the surgical technique, could be other causative factors for RBBB 1151819. Considering these factors, our study indicated that the occurrence of RBBB early within 1 month following HT was less likely to be related with early graft rejection.…”
Section: Discussionmentioning
confidence: 71%
“…The prevalences of RBBB in the present study population were 15.9% at 1 month and 36.5% at 1 year, similar to previous studies (12% to 79%). Most previous studies reported that the development of RBBB and QRS width increased over the time after HT 4131415. Meanwhile, several studies indicated that the occurrence of conduction disorders after HT was related with longer ischemic time, extracorporeal circulation time, surgery-related myocardial damage, and graft rejection 3416.…”
Section: Discussionmentioning
confidence: 99%